High-performance real-time implementation of a spectral estimator - Madeira, M. M. (2015)
Doppler blood flow spectral estimation is a common technique of noninvasive cardiovascular disease detection. Blood flow velocity and disturbance may be evaluated by measuring spectral mean frequency and bandwidth respectively. Aiming at minor stenosis diagnosis, parametric spectral estimators may be employed. These models present better spectral resolution than the FFT based ones, at the expense of higher computational burden. Seeking for an efficient real-time implementation of a blood now spectral estimation system, high performance techniques are being investigated. This paper compares the implementation of the Modified Covariance (MC) spectral estimator on two different DSP architectures: the TMS320C40 and the ADSP2016x (SHARC). Implementations are described and their performance assessed. Considerations about portability of algorithms, compiler optimisation levels and system dependence features are addressed. Copyright (C) 1998 IFAC.